Improved hybrid algorithm for real time sound propagation using intelligent prioritization - Charalampous, Panagiotis; Michael-Grigoriou, Despina (My University, 2016)
We present a hybrid algorithm which combines image source method, ray tracing and intelligent prioritization for faster calculation of impulse responses to be used in real time sound rendering. We use the image source method to calculate sound reflections from specular surfaces and we use a prioritized ray tracing algorithm for fast detection and evaluation of valid image sources from the tree of candidate image sources. Our algorithm delivers improved acoustical results in most cases when compared to a non prioritized version of it, a ray tracing algorithm and a best first image source algorithms, indicating that prioritization can deliver performance gains in real time sound rendering methods.
Keywords: Algorithms; Ray tracing; Sound rendering